Kontribusi Pajak Restoran Dalam Meningkatkan Pendapatan Asli Daerah Kota Kupang - Antonius Nggangga; Debi A. D. Mauwalan; Penina M. Orafeto (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The research problem is: How much does restaurant tax contribute to increasing Kupang City's local revenue? The purpose of this research is to determine the contribution of restaurant tax revenue. The data collection techniques used are documentation and interviews. The data analysis technique is quantitative descriptive using the Contribution Ratio formula. Based on the results of data analysis, it can be concluded that the amount of Restaurant Tax Contribution in Increasing the Original Regional Income of Kupang City in 2019-2023 is categorized as "Less". This is caused by the lack of awareness of restaurant taxpayers in paying taxes and lack of supervision.